THE ABILITY OF THE TENTH GRADE STUDENTS OF SMA NEGERI 5 MODEL PALU IN WRITING DESCRIPTIVE TEXT - Ni Komang Ayu Windari; Sriati Usman; Budi Budi (Tadulako University, 2022)
This research aims to find out the ability of the tenth-grade students of SMA Negeri 5 Model Palu in writing descriptive text. This research used a quantitative research design. By using a random sampling technique, the sample was 30 students of class X MIPA4 and X MIPA6. Data were collected through a writing test. The data were analyzed by using Sudijono’s formula to get the mean scores of the students' ability in writing descriptive text. The result shows that the students' ability in writing descriptive text is in average level with the mean score 63. The mean score of each aspect of writing is different. The highest mean score is on content (84). The other mean scores of the writing aspects are organizing ideas (61), grammar (55), and mechanic (52). Based on these findings, it is suggested to the teachers to give more exercises to the students in order to increase their writing ability, particularly on writing system (grammar and mechanics).